Impact of bottle size on in-home consumption of sugar-sweetened beverages: a feasibility and acceptability study - Eleni Mantzari; Gareth J. Hollands; Rachel Pechey; Susan Jebb; Theresa M. Marteau (BMC, 2017)
Abstract Background Consumption of sugars-sweetened beverages (SSB) increases energy intake and the risk of obesity. Large packages increase consumption of food, implying that smaller bottle sizes may help curb SSB consumption, but there is a lack of relevant evidence relating to these products. This study explores the feasibility and acceptability of conducting a randomised controlled trial to assess the impact of different bottle sizes on SSB consumption at home. Methods Households in Cambridge, England, which purchased at least 2 l of regular cola drinks per week, received a set amount of cola each week for four weeks, in bottles of one of four sizes (1500 ml, 1000 ml, 500 ml, or 250 ml) in random order. The total volume received consisted of a modest excess of households' typical weekly purchasing, but was further increased for half the study households to avoid ceiling effects. Consumption was measured by recording the number of empty bottles at the end of each week. Eligible households were invited to complete a run-in period to assess levels of active participation. Results Thirty-seven of 111 eligible households with an interest in the study completed the run-in period. The study procedures proved feasible. The target for recruitment (n = 16 households) was exceeded. Measuring consumption was feasible: over three quarters (n = 30/37) of households returned all bottles on the majority (n = 88/101) of the study weeks completed across households. The validity of this measure was compromised by guests from outside the household who drank the study cola (n = 18/37 households on 48/101 study weeks) and consumption of the study cola outside the home. Supplying enhanced volumes of cola to nine households was associated with higher consumption (11,592 ml vs 7869 ml). The intervention and study procedures were considered acceptable. Thirteen households correctly identified the study aims. Conclusion The findings support the feasibility and acceptability of running a randomised controlled trial to assess the impact of presenting a fixed volume of SSB in different bottle sizes on in-home consumption. However, methods that avoid consumption being influenced by the amount of cola supplied weekly by the study and that capture out of home consumption are needed before conducting a randomised controlled trial. Trial registration ISRCTN14964130 ; Registered on 18th May, 2015.